2018
DOI: 10.3390/ma12010080
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the MgO/Silica Fume Ratio on the Reaction Process of the MgO–SiO2–H2O System

Abstract: In order to clarify the effect of the MgO–silica fume (SF) ratio on the reaction process of the MgO–SiO2–H2O system, the reaction products and degree of reaction were characterized. Furthermore, the parameters of the reaction thermodynamics were calculated and the reaction kinetics were deduced. The results indicate that a large amount of Mg(OH)2 and small quantities of magnesium silicate hydrate (M–S–H) gels were generated upon dissolution of MgO. However, the M–S–H gels were continuously generated until the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The components of compensating shrinkage can be divided into three categories: Calcium oxide, calcium sulphoaluminate and MgO [25]. Calcium oxide and calcium sulphoaluminate react violently and are not easily controlled in a high alkali environment, thus they cannot achieve a good compensating shrinkage effect in geopolymer [26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…The components of compensating shrinkage can be divided into three categories: Calcium oxide, calcium sulphoaluminate and MgO [25]. Calcium oxide and calcium sulphoaluminate react violently and are not easily controlled in a high alkali environment, thus they cannot achieve a good compensating shrinkage effect in geopolymer [26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that beyond 7 days, the amount of brucite available reduces depending on the initial MgO to SiO 2 ratio. 21 Hence, the reduction in pore volume observed is primarily due to the formation of M-S-H. An increase of 40%-80% in compressive strength has been reported between 7 and 28 days for the MgO-SiO 2 binder system, primarily associated with the precipitation of M-S-H. 3,17 A further reduction in porosity is expected beyond 28 days due to continued hydration reaction. 40 The reduction in porosity, observed in Figure 2, with hydration in this investigation is contrary to some of the existing literature.…”
Section: Evolution With Agementioning
confidence: 94%
“…20 The majority of the research studies conducted uses silica fume (SF) or micro silica as the primary source of SiO 2 alongside MgO. 6,7,21,22 The hydrated M-S-H paste is reported to have a microstructure dominated by pores smaller than 10 nm, as measured using mercury intrusion porosimetry (MIP). 23,24 However, information on the evolution of microstructure with hydration and the effect of initial mix composition is sparse.…”
Section: Introductionmentioning
confidence: 99%
“…According to the TG/DTG analysis, when the initial MS-MR exceeded 1.4, unconsumed Mg(OH) 2 remained in the MAAS after curing for 300 days, indicating that MgO was in excess. When the initial MgO was insufficient, the generation of the M-S-H gel ultimately depended on the amount of incorporated MgO [18].…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Brew [17] found that the molecular structure of the M-S-H gel tends to include a talc structure when magnesium is deficient (Mg 3 (Si 2 O 5 ) 2 (OH) 2 , Mg:Si = 0.75) and tends to adopt a serpentine structure when magnesium is sufficient (Mg 3 (Si 2 O 5 )(OH) 4 , Mg:Si = 1.5). Li [18] found that when the MgO content exceeded 40 wt.%, the final reaction products were M-S-H gel and Mg(OH) 2 , and when the MgO content was less than 40 wt.%, the final reaction products were M-S-H gel and SiO 2 .…”
Section: Introductionmentioning
confidence: 99%